IJSD Volume 8 Editorial: Solo/Screen - Harmony Bench; Simon Ellis (The International Journal of Screendance, 2017)
This volume did not start out as a themed issue, but similarities will emerge among any collection of essays when ideas and authors find themselves in proximity to one another. In our open call, we asked for screendance artists and scholars working at the intersection of film, dance, visual arts, and media arts to "expand and critique contemporary notions of screen-based images and changing choreographic practices, and [to] engage with theories and philosophies from interdisciplinary fields."[^1] An unanticipated commonality emerged among the contributions responding to this open invitation: solo performance. [^1]: "International Journal of Screendance Volume 8: Call for Papers." *Centre for Screendance*. May 17, 2016. <https://screendance.wordpress.com/2016/05/17/international-journal-of-screendance-volume-8-call-for-papers/>
Keywords: screendance; editorial; solo performance; alone